POLICY OF CHINA'S DEBT-TRAP DIPLOMACY: The Influence Of Media In Forming Community Political Opinions - Haderiansyah Haderiansyah; Margareta Habibah; Andri Setiawan; Muzahid Akbar Hayat (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
The term debt-trap or Chinese debt trap originated from the introduction of the Belt and Road Initiative (BRI) policy by Chinese President Xi Jinping in 2013 which aims to connect the Eurasian economy with infrastructure, trade, and investment. Debt trap diplomacy is related to the cases that occurred in Sri Lanka and Pakistan. In Indonesia, the policy on cooperation projects in the infrastructure sector existed before the BRI policy was signed and then increasingly under the BRI banner. However, if seen from the SULNI June 2020 data, the value of Indonesia's debt to China is around 1% and the cooperation is mostly in the field of productive infrastructure. If the policy of Indonesia-China cooperation is carried out properly and continues to be introspective both inside and outside, then development funding under the BRI banner can produce good results and can avoid debt bondage. In Indonesia, where most of the people have negative sentiments towards Chinese policies, this often happens and is framed for political consumption which is disposed of to the public through mass media and then used to lead opinions through discussions on social media.